Association between cerebral blood flow variation and cognitive decline in older patients undergoing hemodialysis - Guo, Yidan; Cui, Wei; Ye, Pengpeng; Luo, Yang (Frontiers in Aging Neuroscience, 2024)
Background The mechanism of cognitive impairment in hemodialysis patients is multifactorial. The relationship between cerebral blood flow and the decline of cognitive function is poorly understood. Objective To investigate the association between cerebral blood flow variation and decline of cognitive function in older patients undergoing hemodialysis. Methods In this prospective observational cohort study of 121 older patients undergoing hemodialysis, we used transcranial Doppler ultrasound (TCD) to measure cerebral arterial mean flow velocity (MFV) throughout dialysis, assessed cognitive function at baseline and 12-month follow-up, and then analyzed associations between MFV and changes on cognitive scores. Results TCD recordings demonstrated a significant reduction in MFV throughout dialysis, which were significantly correlated with cumulative ultrafiltration volume (rho 0.356, p < 0.001), ΔSBP (rho 0.251, p = 0.005), and ΔMAP (rho 0.194, p = 0.032). Compared with the baseline assessments, cognitive scores of participants at the 12-month follow-up were significantly worsened in global cognition (MOCA), some tests of memory (CFT-memory), executive function (TMT-B, SCWT-C, and SCWT-T), attention/processing speed (SDMT), and visuospatial function (CFT-copy) (p < 0.05). The worsening scores in global cognition (MOCA) (β = 0.066, 95% CI 0.018–0.113, p = 0.007) and some tests of memory (AVLT5) (β = 0.050, 95% CI 0.004–0.097, p = 0.035) and executive function (TMT-B, SCWT-C, SCWT-T) (β = 1.955, 95% CI 0.457–3.453, p = 0.011; β = 0.298, 95% CI 0.112–0.484, p = 0.002 and β = 1.371, 95% CI 0.429–2.303, p = 0.004, respectively) were significantly associated with the reduction of MFV. Conclusion Hemodialysis may significantly reduce cerebral blood flow in older patients; Repetitive intradialytic decreases in CBF may be one of the mechanisms underlying the decline of cognitive function. Clinical trial registration https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S000C5B5&selectaction=Edit&uid=U0003QEL&ts=4&cx=-djoi2